Expository report on the overall banking condition, CAMEL based Performance of a Islami Bank in Bangladesh: A case of First Security Islami Bank Ltd. - Mahin, MD. Farhan Abdal (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.